Visualities : perspectives on contemporary American Indian film and art - Cummings, Denise K. (American Indian studies series (East Lansing, Mich.), 2011)
In recent years, works by American Indian artists and filmmakers such as Jaune Quick-To-See Smith, Edgar Heap of Birds, Sherman Alexie, Shelley Niro, and Chris Eyre have illustrated the importance of visual culture as a means to mediate identity in contemporary Native America. This insightful collection of essays explores how identity is created and communicated through Native film-, video-, and art-making; what role these practices play in contemporary cultural revitalization; and how Indigenous creators revisit media pasts and resignify dominant discourses through their work.